2014
DOI: 10.1093/nar/gku613
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger oxidation of Fpg/Nei DNA glycosylases by 2-thioxanthine: biochemical and X-ray structural characterization

Abstract: DNA glycosylases from the Fpg/Nei structural superfamily are base excision repair enzymes involved in the removal of a wide variety of mutagen and potentially lethal oxidized purines and pyrimidines. Although involved in genome stability, the recent discovery of synthetic lethal relationships between DNA glycosylases and other pathways highlights the potential of DNA glycosylase inhibitors for future medicinal chemistry development in cancer therapy. By combining biochemical and structural approaches, the phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 68 publications
(68 reference statements)
8
22
0
Order By: Relevance
“…The compound 2TX was identified in a DNA base analog screening as an uncompetitive inhibitor of the E. coli formamidopyrimidine-DNA glycosylase (EcFpg) [30]. We confirmed the inhibitory effect of 2TX on ZnF-containing enzymes from the Fpg/Nei DNA glycosylase structural superfamily (including LlFpg, EcNei and hNeil2) [18]. Although the precise mode of action of 2TX remains to be clarified, we established in solution and by X-ray analysis that-unexpectedly-2TX chemically and selectively targets the two most exposed cysteine residues of the ZnF in these enzymes.…”
Section: Inhibition Of the Bacterial Fpg Activity By 2tx Derivativessupporting
confidence: 55%
See 3 more Smart Citations
“…The compound 2TX was identified in a DNA base analog screening as an uncompetitive inhibitor of the E. coli formamidopyrimidine-DNA glycosylase (EcFpg) [30]. We confirmed the inhibitory effect of 2TX on ZnF-containing enzymes from the Fpg/Nei DNA glycosylase structural superfamily (including LlFpg, EcNei and hNeil2) [18]. Although the precise mode of action of 2TX remains to be clarified, we established in solution and by X-ray analysis that-unexpectedly-2TX chemically and selectively targets the two most exposed cysteine residues of the ZnF in these enzymes.…”
Section: Inhibition Of the Bacterial Fpg Activity By 2tx Derivativessupporting
confidence: 55%
“…While recent studies have demonstrated the relevance of the research to design innovative anticancer strategies, only a few reported the search for hOgg1 and hNeil1 inhibitors [18][19][20][21]. In previous work, we initiated this study on DNA glycosylases from the structural Fpg/Nei superfamily [18,22,23]. These enzymes recognize and excise oxidized bases in DNA by catalyzing the cleavage of the N-glycosydic bond between the damaged base and its associated sugar.…”
Section: Reactive Oxygen Species (Oh• Omentioning
confidence: 99%
See 2 more Smart Citations
“…40 Similarly, a recently identified Fpg inhibitor also decreased the activity of other closely related DNA glycosylases. 50 Ongoing experiments of OGG1 cocrystallization with these compounds are anticipated to uncover how these molecules display such high specificity.…”
Section: Resultsmentioning
confidence: 99%